A comparison between the views of Jonathan Edwards and John Wesley regarding the sovereignty of God - Robertson, Alan Charles (Rhodes University, Faculty of Divinity, Department of Divinity, 1977)
The views of Edwards and Wesley regarding the sovereignty of God present a puzzle. On the face of things, both were successful evangelists while both held contrary doctrines of sovereignty. Does this mean that the doctrine of sovereignty is irrelevant? This thesis argues that the doctrine of sovereignty is crucial in evangelism and revival, and that the views of Edwards and Wesley regarding the sovereignity of God were in fact very similar. A useful framework for showing this is the Five Points of Calvinism, as well as the doctrines of justification by faith and the omnipotence of God.
Keywords: Edwards, Jonathan, 1703-1758; Wesley, John, 1703-1791; Free will and determinism; Predestination -- History of doctrines; God -- Omniscience -- History of doctrines; Atonement